The Effectiveness of Acceptance and Commitment Therapy on Anxiety, Depression, and Stress in Patients with Spinal Cord Injuries - Torabian, Saharalsadat; Hemmati Sabet, Vahid; Meschi, Farahnaz (International Clinical Neuroscience Journal, 2019)
Background: Since the number of patients with spinal cord injuries is increasing, paying attention to these patients’ psychological problems is a priority. This study aimed to evaluate the effect of acceptance and commitment therapy on anxiety, depression, and stress in patients with spinal cord injuries. Methods: The present study had utilized a single-subject approach in the form of multiple baseline design. The samples were selected using purposive sampling based on convenience sampling method. The statistical population included all patients in Hamadan city with spinal cord injuries who referred to the Shahid Beheshti hospital in this city. The total numbers of them were 181 people in 2016. The researchers informed the patients about the research and presented them with informed consent forms. Among 50 screened patients, five patients (4 males and one female) selected and entered the treatment process: anxiety, depression, and stress measured by Depression Anxiety Stress Scales (DASS-21). Acceptance and commitment therapy conducted in 8 treatment sessions on anxiety, depression, and stress in patients with spinal cord injuries. Results: The results of the graphic and chart analysis, reliable change index (RCI) and the percentage of recovery showed that acceptance and commitment therapy affected anxiety, depression, and stress in the patients with spinal cord injuries. Conclusion: Findings indicated that acceptance and commitment therapy improved people’s mental health by working on acceptance and mindfulness processes and behavior change processes. This therapy decreased anxiety, depression, and stress in patients with spinal cord lesion.